2020
DOI: 10.3390/nu12061659
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Their Effect on Blood Pressure—A Review

Abstract: Elevated blood pressure affects a great part of the elderly population and is the leading risk factor for cardiovascular disease. New approaches have been taken in the fight against this growing problem, in the form of diets (Mediterranean, Dietary Approaches to Stop Hypertension (DASH) and intermittent fasting). Recent research has shown the promising results regarding diets and their effect on the prevention and improvement of elevated blood pressure. This review attempts to take this a step further, reviewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Another study by reviewing the literature illustrated a good evidence of the BP-lowering effect of bioactive compounds such as lycopene, docosahexaenoic acid, and dietary fiber which are high in DASH dietary pattern. 47 Indeed, a systematic review and meta-analysis in 2020 indicates that DASH diet could significantly increase glutathione and decrease malondialdehyde levels, with a trend to improve total antioxidant capacity (TAC), nitric oxide, and f2-isoprostanes by the adherence to the DASH diet. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Another study by reviewing the literature illustrated a good evidence of the BP-lowering effect of bioactive compounds such as lycopene, docosahexaenoic acid, and dietary fiber which are high in DASH dietary pattern. 47 Indeed, a systematic review and meta-analysis in 2020 indicates that DASH diet could significantly increase glutathione and decrease malondialdehyde levels, with a trend to improve total antioxidant capacity (TAC), nitric oxide, and f2-isoprostanes by the adherence to the DASH diet. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacological therapies, including lifestyle improvement and dietary modification, and pharmacological treatments, including antihypertensive, lipid-lowering and antidiabetic medications are the cornerstone of cardiovascular disease prevention. While antioxidants such as carotenoids have not been directly used in the treatment of hypertension, dietary modifications (including the Approaches to Stop Hypertension (DASH) and Mediterranean diets) that recommend regular consumption of carotenoid-rich fruits and vegetables clearly play a role in lowering BP and have been officially endorsed by health organizations (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding arterial remodeling and atheromatosis, it was highlighted that there is scarce evidence, which does not allow solid conclusions. Lastly, the Special Issue also included another review by Malinowski et al that examined the available evidence on the effect of a range of dietary compounds on blood pressure levels [ 9 ]. This review reported that there is good evidence suggesting the blood pressure-lowering effect of lycopene, docosahexaenoic acid (i.e., omega-3 fatty acid), epigallocatechin-3-gallate (i.e., a type of catechin found in tea) and dietary fibre, although further studies are required to strengthen these findings.…”
mentioning
confidence: 99%